Genome‐wide association studies for milk production traits in Valle del Belice sheep using repeated measures. (14th April 2019) - Sutera, A. M.; Riggio, V.; Mastrangelo, S.; Di Gerlando, R.; Sardina, M. T.; Pong‐Wong, R.; Tolone, M.; Portolano, B.
Summary: Genome‐wide association studies (GWASes) have become a powerful tool for identifying genomic regions associated with important traits in livestock. Milk production traits in dairy sheep are measured at different time points during their life span. Using phenotypic data generated from longitudinal traits could improve the power of association studies but until now have received less attention in GWASes as a methodology and has not been implemented. The aim of this study was to carry out a GWAS for milk production traits in Valle del Belice sheep using repeated measures. After quality control, 469 ewes and 37 228 SNPs were retained for the analysis, and phenotypic data included 5586 test‐day records for five milk production traits (milk yield, MY; fat yield and percentage, FY and F%; protein yield and percentage, PY and P%). Nine SNPs located within or close to known genes were found to be associated with milk production traits. In particular, rs398340969, associated with both milk yield and protein yield, is located within the DCPS gene. In addition, rs425417915 and rs417079368, both associated with both fat percentage and protein percentage, are located within the TTC7B gene and at 0.37 Mb within the SUCNR1 gene respectively. In summary, the use of repeated records was beneficial for mapping genomic regions affecting milk production traits in the Valle del Belice sheep.